2021
DOI: 10.1016/j.ejvs.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Deep Femoral Vein Reconstruction for Abdominal Aortic Graft Infections is Associated with Low Aneurysm Related Mortality and a High Rate of Permanent Discontinuation of Antimicrobial Treatment

Abstract: WHAT THIS PAPER ADDSThis paper describes the experience of in situ reconstruction of aortic graft and endograft infections using autologous deep femoral vein and reports overall favourable patient outcomes from the procedure. In particular, the explantation of infected aortic endografts was not associated with increased mortality and morbidity, and freedom for antibiotic therapy after one year was high, indicating a high curative treatment rate. Post-operative renal damage was limited, even in patients in need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Most importantly, it is a very complex and time-consuming procedure. According to a recent study, the mean operating time for this surgery was 645 minutes, which was much longer than the time reported in this present study (433 minutes) [ 28 ]. In our study, banked allograft was used only in the case with intraabdominal sepsis because of limited availability.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Most importantly, it is a very complex and time-consuming procedure. According to a recent study, the mean operating time for this surgery was 645 minutes, which was much longer than the time reported in this present study (433 minutes) [ 28 ]. In our study, banked allograft was used only in the case with intraabdominal sepsis because of limited availability.…”
Section: Discussioncontrasting
confidence: 56%
“…Some authors reported that reconstruction with an allograft or autologous femoral vein has the advantage of reduced rates of infection. However, aortic reconstruction with an allograft must be performed only at a hospital with a tissue bank, and where commercial products have limited availability and/or costlier [ 27 28 29 ]. Additionally, reconstruction with an autologous femoral vein has some disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Extra-anatomic bypass with aortic ligation is another strategy. However, it includes the risk of aortic stump rupture 12 and the disadvantage of requiring long-term anticoagulation therapy. Therefore, we performed an aorto-uni type revascularization using a bovine pericardial roll and FF bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a number of proposed therapeutic approaches, a clear therapeutic plan is yet to be defined. There are various techniques described in the literature, including in situ reconstruction with prosthetic materials or deep femoral vein reconstruction with the neo-aorto-iliac system (NAIS), while other authors propose graft excision and extra-anatomic bypass [ 7 , 12 , 13 ]. The significantly worse outcome of patients presenting in hemorrhagic shock and the development of endovascular techniques in the last several years raises the question of whether stent-graft implantation can effectively minimize the perioperative risk in patients presenting with acute life-threatening bleeding [ 14 ].…”
Section: Discussionmentioning
confidence: 99%